2013
DOI: 10.1002/aenm.201201038
|View full text |Cite
|
Sign up to set email alerts
|

Improved Black Silicon for Photovoltaic Applications

Abstract: The morphology and the electronic properties of monocrystalline Si (c‐Si) with a nano‐textured “black” surface, obtained by a metal‐catalyzed wet etching process, and the improvement by an additional chemical treatment are examined with regard to solar cell applications. Photoluminescence and optical reflectivity measurements show the presence of a nano‐porous Si (np‐Si) phase in the as‐prepared nano‐texture. It is found that an additional wet chemical treatment with the standard clean 1 of the common RCA clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…In this review article, we focus on the four most prominent fabrication methods of b-Si: dry reactive ion etching in an inductive coupled plasma (ICP-RIE), [ 15,46,51 ] electroless MACE with Ag [ 3,35,57 ] and Au [ 1,58 ] catalysts, photoelectrochemical anodization that leads to the formation of macP-Si, [ 12 ] and the irradiation of the surface with femtosecond (fs) laser pulses (L-Si) in vacuum. [ 39,40 ] The various black etching methods ( Figure 1 ) all lead to homogeneous macroscopically b-Si surfaces with a rather low refl ectance over the whole absorbing range of silicon as will be shown in section 1.8.…”
Section: Fabrication Methods For Black Siliconmentioning
confidence: 99%
See 2 more Smart Citations
“…In this review article, we focus on the four most prominent fabrication methods of b-Si: dry reactive ion etching in an inductive coupled plasma (ICP-RIE), [ 15,46,51 ] electroless MACE with Ag [ 3,35,57 ] and Au [ 1,58 ] catalysts, photoelectrochemical anodization that leads to the formation of macP-Si, [ 12 ] and the irradiation of the surface with femtosecond (fs) laser pulses (L-Si) in vacuum. [ 39,40 ] The various black etching methods ( Figure 1 ) all lead to homogeneous macroscopically b-Si surfaces with a rather low refl ectance over the whole absorbing range of silicon as will be shown in section 1.8.…”
Section: Fabrication Methods For Black Siliconmentioning
confidence: 99%
“…[ 58 ] It was also shown that the lifetime could be increased by about one order of magnitude if the SC1 was carried out after MACE and before Al 2 O 3 deposition by plasma-assisted ALD. A possible explanation is a defect-rich layer or contamination with deep-level impurities originating from the MACE process that cannot be passivated with Al 2 O 3 .…”
Section: Analysis Of the Origin Of Recombination-active Surface Defecmentioning
confidence: 98%
See 1 more Smart Citation
“…Depositing a-Si:H on the as-processed Si MPs+NPs substrate resulted in a shunted device. Therefore, during i-a-Si:H deposition, the high dangling bond density on the (100) plane wafer reducing the a-Si:H precursor diffusion coefficient, resulting high-defects Si thin films occurs more readily on high-defect-density (100) planes than on (111) planes [22,23] . To ensure high Voc values, one needs to fabricate the interface carefully, so that it allows for effective carrier collection; this is not the case with defective interfaces and those corresponding to high Sit values.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 In addition, a simple femtosecond-laser (fs-laser) processing technique can drastically change the optical properties of silicon. In particular, the fs-laser processed silicon (black silicon) has gained increased interest due to the peculiar optical properties, including the enhanced sub-bandgap absorption [11][12][13] and visible light emission. 14,15 In this work, we carry out cathodoluminescence spectroscopy and imaging in the scanning electron microscope (SEM-CL) and in the scanning transmission electron microscope (STEM-CL) to determine the black silicon light emission properties from the microscale to the nanoscale.…”
mentioning
confidence: 99%